Analysis of EU free trade agreements as one of the tools of EU economic diplomacy (Economics and region, 2023)
The article summarizes the features of the the EU economic diplomacy model functioning. It was determined that the main EU institutions in the field of economic diplomacy are the European Parliament, the European Commission and the European External Affairs Service, which have functions that contribute to the implementation of EU economic diplomacy. It has been established that a common form of trade and economic relations between countries and regional associations is cooperation on the basis of free trade agreements (FTA). Hence, EU free trade agreements were analyzed and a regression analysis of the impact of EU free trade zones with other countries on EU GDP was carried out. It was determined that free trade agreements are an effective tool of economic diplomacy. It has been established that the EU has the largest trade network in the world, with more than 40 separate agreements with countries and regions that facilitate trade in products and services between the EU and its external partners. The latest EU agreements and the dynamics of trade within them were studied (the EU-Canada Comprehensive Economic Trade Agreement (2017), the EU-Singapore Free Trade Agreement (2018), the EU-Japan Economic Partnership Agreement (2019). The annual Eurostat international trade in goods datas from 2018 to 2022 were analyzed. It was found that the COVID-19 pandemic had a negative impact on the export-import operations of the EU with Canada, Singapore and Japan during 2020. The authors used the Scatter plot model and performed regression analysis for determining which free trade area (EU-Canada, EU-Singapore or EU-Japan) affects EU GDP growth. The research model confirms a positive relationship between EU GDP growth and the growth of foreign trade turnover (FTT) between EU and Canada, EU and Japan. Regression analysis shows that 96% (EU-Canada) and 90% (EU-Japan) of changes in EU GDP are explained by changes in FTAs with the respective countries. It is proved that changes in the FTA between the EU and Singapore do not affect the state of EU GDP. It was concluded that free trade agreements contribute to the development of EU trade with other countries of the world and have a positive effect on the growth of the Union's GDP.
Keywords: free trade zone; economic diplomacy; Eurostat; foreign trade; export; import